2017
DOI: 10.1155/2017/7210591
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Temperature Curing Methods on the Compressive Strength Development of Concrete Containing High Volumes of Ground Granulated Blast-Furnace Slag

Abstract: This paper investigates the effect of the high-temperature curing methods on the compressive strength of concrete containing high volumes of ground granulated blast-furnace slag (GGBS). GGBS was used to replace Portland cement at a replacement ratio of 60% by binder mass. The high-temperature curing parameters used in this study were the delay period, temperature rise, peak temperature (PT), peak period, and temperature down. Test results demonstrate that the compressive strength of the samples with PTs of 65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Hiremath et al [46] studied the development of early strength of shotcrete under the conditions of hot water bath and hot air curing; they found that the early strength of shotcrete showed an upward trend with the increase of temperature and that hot water bath Hiremath et al [46] studied the development of early strength of shotcrete under the conditions of hot water bath and hot air curing; they found that the early strength of shotcrete showed an upward trend with the increase of temperature and that hot water bath curing was conducive to the development of early strength of shotcrete. Wonsuk et al [47] studied slag shotcrete and found that under high-temperature conditions, the output of CO 2 in cement decreased and the early strength of shotcrete was significantly improved. The linear expansion value of slag shotcrete is very low and the pozzolanic activity is high, which is conducive to the development of shotcrete strength at the later stage [48].…”
Section: Influence Of High Temperature On Shotcrete Structurementioning
confidence: 99%
“…Hiremath et al [46] studied the development of early strength of shotcrete under the conditions of hot water bath and hot air curing; they found that the early strength of shotcrete showed an upward trend with the increase of temperature and that hot water bath Hiremath et al [46] studied the development of early strength of shotcrete under the conditions of hot water bath and hot air curing; they found that the early strength of shotcrete showed an upward trend with the increase of temperature and that hot water bath curing was conducive to the development of early strength of shotcrete. Wonsuk et al [47] studied slag shotcrete and found that under high-temperature conditions, the output of CO 2 in cement decreased and the early strength of shotcrete was significantly improved. The linear expansion value of slag shotcrete is very low and the pozzolanic activity is high, which is conducive to the development of shotcrete strength at the later stage [48].…”
Section: Influence Of High Temperature On Shotcrete Structurementioning
confidence: 99%
“…Although these three SCMs have little influence on hydration products, they can improve the sulfate resistance of steam-cured concrete. However, compared with the SCMs mentioned above, ground blast furnace slag (GBFS) is the most widely used in prefabricated components at present [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…However, with the deep development of underground engineering, high temperature is often seen in tunnel and mine construction. [5][6][7] On the one hand, it is due to the violent movement of magma, and on the other hand, surface water and original groundwater are heated by deep high-temperature rock masses to form high hot spring water and steam, which continuously release heat, resulting in a sharp increase of heat in construction roadway space. [8][9][10][11] Whereas, as a kind of heterogeneous brittle mixed material, when the ambient temperature exceeds the temperature that the shotcrete can resist, the concrete structure will crack, [12][13][14] resulting in great changes in the durability, heat insulation and adhesion of the shotcrete.…”
Section: Introductionmentioning
confidence: 99%
“…As an advanced geotechnical engineering construction technology, shotcrete (New Austrian Tunneling Method) is widely used in underground engineering, such as mine roadway, railway (highway) tunnel, subway and so on, for roadway surrounding rock control and support 1–4 . However, with the deep development of underground engineering, high temperature is often seen in tunnel and mine construction 5–7 . On the one hand, it is due to the violent movement of magma, and on the other hand, surface water and original groundwater are heated by deep high‐temperature rock masses to form high hot spring water and steam, which continuously release heat, resulting in a sharp increase of heat in construction roadway space 8–11 .…”
Section: Introductionmentioning
confidence: 99%